LESBIAN CONTINUUM AS AN ALTERNATIVE STRATEGY IN NEGOTIATING HETERONORMATIVITY IN SARAH WATER’S FINGERSMITH - Erwanti, Mega Hayuningtyas; Maimunah, Maimunah (ATAVISME, 2015)
This study is conducted to examine the portrayal of a lesbian continuum in Sarah Waters? Fingersmith. To conduct the analysis, there are two research questions: first, how is the construction of lesbian continuum portrayed in the relationship between Susan Trinder and Maud Lilly and how does lesbian continuum become a strategy to negotiate compulsory heterosexuality. In doing the analysis, the theory of lesbian continuum which is proposed by Adrienne Rich will be used to elaborate the novel. This study is a qualitative research where the data are taken from the novel Fingersmith, library research, journals, and other relevant sources. To gain the comprehensive analysis, this study uses some methods which are: close reading, postulation the statements of the problems, data classification, and analysis using the lesbian continuum theory, supporting analysis through library research, books, and academic journals. This study finds that the characters of Susan Trinder and Maud Lilly can be identified as having a double life which constructs the lesbian continuum. Moreover, the lesbian continuum becomes a strategy to negotiate compulsory heterosexuality with denial and negotiation of women?s oppression. Abstrak: Artikel ini mengkaji representasi lesbian continuum dalam novel Sarah Waters yang berjudul Fingersmith. Dua pertanyaan utama penelitian ini adalah (1) bagaimana konstruksi lesbian continuum direpresentasikan dalam hubungan antara tokoh Susan Trinder dan Maud Lily dalam novel Fingersmith dan (2) bagaimana lesbian continuum menjadi strategi untuk menghadapi compulsory heterosexuality dalam novel Fingersmith. Teori lesbian continuum oleh Adrienne Rich akan menjadi teori utama untuk menjawab pertanyaan penelitian. Menggunakan teknik pembacaan novel dan analisis pustaka yang bersumber dari jurnal dan sumber lain yang mendukung. Untuk mendapatkan data yang komprehensip, metode yang dipakai adalah close reading, menjabarkan pertanyaan, klasifikasi data, dan analisis menggunakan teori lesbian continuum, analisis didukung menggunakan penelitian pustaka, buku dan jurnal. Dalam penelitian ini dapat disimpulkan hal-hal berikut: Pertama, tokoh Susan Trinder dan Maud Lily diidentifikasi memiliki kehidupan ganda (double life), yang merupakan ciri dari representasi Lesbian Continuum. Kedua, lesbian continuum adalah strategi untuk bertahan dalam masyarakat dengan cara menyangkal (denial) adanya relasi seksual di antara mereka dan untuk melawan tekanan terhadap perempuan pada masa itu. Kata-kata Kunci: compulsory heterosexuality; lesbian continuum; Fingersmith